Social integration, solidarity, and psychological health of internally displaced persons in Cameroon: Exploring the role of community satisfaction - Angwi Enow Tassang; Shi Guoqing; Tosin Yinka Akintunde; Muhideen Sayibu; Stanley Oloji Isangha; Adekunle Adedeji; Taha Hussein Musa (Heliyon, 2023)
Background/Introduction: Conflict-induced displacement continue to be a pressing public policy concern due to the adverse effects on the well-being of internally displaced persons (IDPs). Understanding the integration process of these individuals, particularly the role of solidarity and social integration in fostering a sense of belonging and improving their community experiences and psychological well-being, remains unclear. This study investigates the role of community satisfaction in the relationship among social integration, solidarity, and psychological health of IDPs in Cameroon. Methods: Cross-sectional data from 428 displaced individuals in the Ntui subdivision, Cameroon, were analyzed using structural equation modeling (SEM). This technique tested four latent variables: social integration, solidarity, community satisfaction, and psychological health. Results: The results show a direct association between solidarity and both community satisfaction (β = 0.282; p < 0.001) and psychological health (β = 0.137; p < 0.01). Community satisfaction also has a direct relationship with the psychological health of the IDPs (β = 0.292; p < 0.001). An indirect effect of solidarity on psychological health through community satisfaction was observed (β = 0.084 (SE = 0.025, CI = [0.047, 0.129], p < 0.001)). However, no mediational effect of community satisfaction was found on the association between social integration and psychological health. The model accounted for 7% of the variance in community satisfaction (R2 = 0.07) and 20% of the variance in psychological health (R2 = 0.20). Conclusion: The findings indicate a strong sense of solidarity among the displaced persons in the studied communities in Cameroon, which promotes their psychological health via community satisfaction. As such, interventions should aim to foster solidarity among displaced persons to enhance their community experiences and psychological health.